2009
DOI: 10.1542/peds.2008-2348
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Hepatic Transaminases to Recognize Abuse in Children

Abstract: In the population of children with concern for physical abuse, abdominal injury is an important cause of morbidity and mortality, but it is not so common as to warrant universal imaging. Abdominal imaging should be considered for potentially abused children when either the AST or ALT level is >80 IU/L or with abdominal bruising, distention, or tenderness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…Most important, because their investigation was ancillary to a larger multicenter study, 13 the authors were unable to determine the effect of their recommendations on clinical practice. As part of the parent study, data were available on 1676 children who underwent evaluation for suspected physical abuse.…”
Section: A B U S I V E H E a D T R A U M A (Aht) Is The Leading Causementioning
confidence: 99%
“…Most important, because their investigation was ancillary to a larger multicenter study, 13 the authors were unable to determine the effect of their recommendations on clinical practice. As part of the parent study, data were available on 1676 children who underwent evaluation for suspected physical abuse.…”
Section: A B U S I V E H E a D T R A U M A (Aht) Is The Leading Causementioning
confidence: 99%
“…[6][7][8] Several diagnostic studies (eg, skeletal survey [SS], neuroimaging, hepatic transaminases, and retinal examination) can identify occult abusive injuries and improve abuse recognition and diagnosis. [9][10][11][12][13][14][15] However, use of these studies has been shown to be widely variable, and to be affected by practice setting, race, and socioeconomic status. 16,17 Twice as many children with highrisk injuries are recognized as abused in children's hospitals than in general hospitals, 18 and abusive fractures are 7 times more likely to be missed in general emergency departments (EDs) than in pediatric EDs.…”
mentioning
confidence: 99%
“…Online discussion comments provided insight into the decisionmaking reflected in the process of consensus development. 20 Some were surprised by practices recommended by other participants, including, "Neck imaging in children with head injury … is this something that everyone is already doing?" 21 Participants also considered the role of CAP evaluations in future research: "In regard to race/ethnicity, how great would it be for research if all CAP reports had this available.…”
Section: Consensus Guideline Developmentmentioning
confidence: 99%